2023
DOI: 10.1097/yco.0000000000000842
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes for the diagnosis and treatment of dementia

Abstract: Purpose of reviewDementia is a syndrome with several possible pathologies. To date, definitive methods for diagnosis and treatment of sub-types of dementia have not been established. Emerging evidence suggests that exosomes can provide important information for the diagnosis and treatment of several subtypes of dementia. This article reviews recent studies on the application of exosomes in dementia.Recent findingsExosomes are involved in the pathogenesis of Alzheimer's disease (AD) and Parkinson's disease (PD)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 78 publications
0
4
0
Order By: Relevance
“…Consequently, the investigation of MSC-EVs is of significant interest. MSC-EVs not only contain abundant bioactive molecules but also function as vital mediums for information transfer between cells ( Joo et al, 2023 ). They are believed to have a central role in VD diagnosis and treatment; for instance, MSC-EVs can deliver neuroprotective factors that encourage neuronal survival and repair, thus reducing neuronal damage and VD severity ( Ma et al, 2022 ).…”
Section: Role and Application Of Msc-evs In The Pathophysiological Pr...mentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, the investigation of MSC-EVs is of significant interest. MSC-EVs not only contain abundant bioactive molecules but also function as vital mediums for information transfer between cells ( Joo et al, 2023 ). They are believed to have a central role in VD diagnosis and treatment; for instance, MSC-EVs can deliver neuroprotective factors that encourage neuronal survival and repair, thus reducing neuronal damage and VD severity ( Ma et al, 2022 ).…”
Section: Role and Application Of Msc-evs In The Pathophysiological Pr...mentioning
confidence: 99%
“…There is a growing interest in EVs as potential diagnostic agents reflecting disease states ( Joo et al, 2023 ). MSC-EVs carry a plethora of bioactive molecules, which may serve as potential biomarkers for early diagnosis and disease monitoring.…”
Section: Potential Role Of Mesenchymal Stem Cell Extracellular Vesicl...mentioning
confidence: 99%
“…However, achieving this precision in exosome detection remains a challenging task and demands extensive investigative efforts. Research indicates that exosomes derived from MSCs possess immense potential for mitigating disease pathologies and enhancing cognitive function in patients with conditions such as Alzheimer's disease, Parkinson's disease and vascular dementia (92). Prospective studies must further explore the concentration of exosomes, establish a specific diagnostic threshold and define the applicable range of pertinent markers to facilitate a more precise foundation for clinical diagnosis.…”
Section: The Progression Of Gastric Cancer Based On Exosomesmentioning
confidence: 99%
“…Additionally, in mouse models, Alvarez‐Erviti et al demonstrated RVG‐targeted exosomes were able to deliver GAPDH siRNA specifically to neurons, microglia and oligodendrocytes with significant knockdown of BACE1 , a target for AD (Alvarez‐Erviti et al, 2011). There has also been recent success in the use of mesenchymal stem cell‐derived exosomes and their ability to ameliorate pathology and improve cognitive function in VAD and AD (Joo et al, 2023; Wang et al, 2023). This potential use of exosomes to deliver therapeutics across the BBB could open new CNS treatment options, if properly explored.…”
Section: Bbb Dysfunction In Dementiamentioning
confidence: 99%